Detection of waste's layers with geoelectric methods: case of Rio Azul sanitary landfill, Costa Rica - Suárez, Jorge (2011)
The Río Azul Landfill received waste for 34 years from various parts of the Greater Metropolitan Area, and for three decades was operated with a poorly planned waste disposal. The purpose was to identify areas of greatest potential leachate storage, making 25 VES (Vertical Electrical Soundings), whose effective exploration depth was around 65 meters. The proposed geophysical model consists of four layers: the first corresponds to a coverage of com- pacted material (20 Ωm - 54 Ωm), the second layer contains unsaturated waste (11 Ωm - 18 Ωm), the third (1 Ωm - 5.4 Ωm) is saturated waste with leachate and the fourth (49 Ωm - 360 Ωm) the basement on which was installed the landfill. Therefore, the geoelectric allowed determining the thickness and distribution of covering materials, waste, saturated waste with leachates and depth of the basement’s top.